Anteromedial thalamic infarct: a rare presentation. (2nd May 2018) - Shabbir, Syed H; Nadeem, Faryal; Labovitz, Daniel
Abstract : We report a rare presentation of an anteromedial thalamic infarct in a 50-year-old woman with acute onset left eye ptosis, vertical gaze paresis and confusion. MRI identified an acute left anteromedial thalamic infarct with a severe left P1 stenosis. Thalamic infarcts are associated with marked neurobehavioural disturbances with dominant thalamic lesions causing language deficits, verbal perseveration, memory disturbances, abulia and disorientation. Ocular movement deficits can also be present and typically accompany paramedian lesions. Rarely, patients can develop an ipsilateral ptosis. We discuss these symptoms and review the literature.